Solving the team orienteering problem : developing a solution tool using a genetic algorithm approach - Ferreira, João Amaro Oliveira (2014)
Comunicação publicada no Livro de Atas: Proceedings of the 17th Online World Conference on Soft Computing in Industrial Applications.